Star formation rates and efficiencies in the Galactic Centre - Barnes, Ashley Thomas; Kruijssen, Diederik (Arxiv, 2017)
The inner few hundred parsecs of the Milky Way harbours gas densities, pressures, velocity dispersions, an interstellar radiation field and a cosmic ray ionisation rate orders of magnitude higher than the disc; akin to the environment found in star-forming galaxies at high-redshift. Previous studies have shown that this region is forming stars at a rate per unit mass of dense gas which is at least an order of magnitude lower than in the disc, potentially violating theoretical predictions. We show that all observational star formation rate diagnostics - both direct counting of young stellar objects and integrated light measurements - are in agreement within a factor two, hence the low star formation rate is not the result of the systematic uncertainties that affect any one method. As these methods trace the star formation over different timescales, from $0.1 - 5$ Myr, we conclude that the star formation rate has been constant to within a factor of a few within this time period. We investigate the progression of star formation within gravitationally bound clouds on $\sim$ parsec scales and find